Development of Parallel Auditory Thalamocortical Pathways for Two Different Behaviors - Razak, Khaleel A.; Fuzessery, Zoltan M. (Frontiers in Neuroanatomy, 2010)
Auditory thalamocortical connections are organized as parallel pathways that originate in different divisions of the medial geniculate body (MGB). These pathways may be involved in different functions. Surprisingly little is known about the development of these connections. Here we review studies of the organization and development of auditory thalamocortical pathways in the pallid bat. The pallid bat depends primarily on passive hearing of prey-generated noise for localizing prey, while reserving echolocation for general orientation and obstacle avoidance. In the inferior colliculus (IC) and the auditory cortex, physiological studies show that noise and echolocation calls are processed in segregated regions. Injection of retrograde tracers in physiologically characterized cortical sites show that the ventral division of the MGB (MGBv) projects to the cortical region selective for noise. The cortical region selective for echolocation calls receives input from the suprageniculate (SG) nucleus in the dorsal MGB, but not from the MGBv. Taken together, these studies reveal parallel IC-MGB-cortex pathways involved in echolocation and passive listening. There is overlap of thalamocortical pathways during development. At two weeks postnatal, when the bat begins to exhibit adult-like hearing thresholds, the SG projects to both noise- and echolocation call-selective regions. The MGBv, as in adults, projects only to the noise-selective region. The connections become adult-like only after two months postnatal. These data suggest that parallel auditory thalamocortical pathways may segregate in an experience-dependent fashion, a hypothesis that remains to be tested in any species.